2014
DOI: 10.1590/s0080-623420140000600004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prenatal care in unit with family health strategy

Abstract: INTRODUCTIONPrenatal care (PN) may contribute to more favorable maternal and perinatal outcomes by enabling early detection and timely treatment of various diseases; in addition to the control of some risk factors that cause complications to women's health and that of newborns (1) .In Brazil, although infant mortality rates have decreased in recent decades, this decline has been uneven across states and municipalities, as well as between areas of a specific municipality (2,3) . To improve national rates and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
7
0
5
Order By: Relevance
“…She was the one that most often listened to their worries during the pregnancy and who gave them security and peace of mind. In line with our results, Corrêa et al (23) found that women placed a high value on the preparation and competence of midwives who helped them to cope with their psychological and emotional needs as well as with those of their partner. They wanted the midwives to listen to them and to treat them as individuals.…”
Section: Discussionsupporting
confidence: 92%
“…She was the one that most often listened to their worries during the pregnancy and who gave them security and peace of mind. In line with our results, Corrêa et al (23) found that women placed a high value on the preparation and competence of midwives who helped them to cope with their psychological and emotional needs as well as with those of their partner. They wanted the midwives to listen to them and to treat them as individuals.…”
Section: Discussionsupporting
confidence: 92%
“…O empreendimento de aferir o perfil e os aspectos dos enfermeiros no processo assistencial da atenção pré-natal transita pela precisão em ponderar e avaliar o panorama e as qualidades das atividades executadas, mediante a tomada de novas decisões. 7,8 Os O cuidado integral e humanizado, oferta de insumos necessários e a intervenção precoce diante certos sinais e sintomas realizados pela enfermagem devem contribuir de maneira significativa para que haja efetividade nos modelos preconizados pelo MS, propendendo à melhoria nos indicadores de morbi-mortalidade. 15 Por sua vez, auxiliando tais indicadores, as ações educativas no decorrer do ciclo gravídico-puerperal, torna-se ferramenta importante, particularmente, no pré-natal, por orientar a mulher na futura vivência do parto de forma positiva, com menor risco de complicações no puerpério, desencadeando maior sucesso no cuidado com o bebê.…”
Section: Discussionunclassified
“…O que podem interferir no acompanhamento é a não adesão ao uso da medicação prescrita para o período gestacional de acordo com a necessidade, e as dificuldades em agendar/realizar os exames solicitados. 7,8 As consultas do pré-natal de baixo risco devem ser realizadas mensalmente e apesar da gestação ser entendida como um processo fisiológico e que na grande maioria das vezes transcorre sem complicações, são preconizadas pelo Ministério da Saúde -MS, no mínimo seis consultas. 9 Assim, as mulheres que não apresentam complicações no decorrer da gravidez são classificadas como grupo de gestantes de baixo risco e as que desenvolvem problemas durante o período gestacional ou evoluem com potenciais complicações para a mãe e feto compõe o grupo de gestantes de alto risco.…”
Section: Introductionunclassified
“…The improvement of prenatal care quality in Brazil could prevent those maternal and infant deaths considered to be preventable. This demands evaluating health services in order to qualify that care (19) . Most of the women in this study had no addiction; however, among those with some addiction the risk of death of the child has clearly doubled.…”
Section: Discussionmentioning
confidence: 99%